2023
DOI: 10.1128/spectrum.01002-23
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Activities of Novel Therapeutic Agents against Molecularly Characterized Clinical Carbapenem-Resistant Enterobacterales Isolates

Abstract: This study determined the susceptibilities of carbapenem-resistant Enterobacterales isolates to various novel antimicrobial agents (ceftazidime-avibactam, imipenem-relebactam, meropenem-vaborbactam, eravacycline, and plazomicin). Whole-genome sequencing was performed for all strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…If we interpret these values by EUCAST breakpoints (for E. coli, ≤0.5 mg/L susceptible category) [17], only three isolates can be determined to be susceptible, which indicates the need to harmonize breakpoints between the two standards. Our results were similar to the results obtained in Singapore (89.6% susceptibility with FDA criteria) [48] and Greece (80.5% susceptibility rate) [30]. The EUCAST breakpoints for E. coli are supposed to be more relevant, as some researchers reported therapeutic success if MICs were below 0.5 mg/L [4,49].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…If we interpret these values by EUCAST breakpoints (for E. coli, ≤0.5 mg/L susceptible category) [17], only three isolates can be determined to be susceptible, which indicates the need to harmonize breakpoints between the two standards. Our results were similar to the results obtained in Singapore (89.6% susceptibility with FDA criteria) [48] and Greece (80.5% susceptibility rate) [30]. The EUCAST breakpoints for E. coli are supposed to be more relevant, as some researchers reported therapeutic success if MICs were below 0.5 mg/L [4,49].…”
Section: Discussionsupporting
confidence: 89%
“…Other authors have also reported similar findings. Teo et al reported 53.4% susceptibility to eravacycline and 89.6% to tigecycline [48]. Higher levels of susceptibility to tigecycline and eravacycline (89% and 85.7% respectively) have been reported by authors from China [52].…”
Section: Discussionmentioning
confidence: 95%